Investigation by HPLC of the Catabolism of Recombinant Tissue Plasminogen Activator in the Rat - Harris, Roy; Frade, Louis Garcia; Creighton, Lesley J; Gascoine, Paul S; Alexandroni, Maher M; Poole, Stephen; Gaffney, Patrick J (Thrombosis and Haemostasis, 1988)
The catabolism of recombinant tissue plasminogen activator (rt-PA) was investigated after injection of radiolabelled material into rats. Both Iodogen and Chloramine T iodination procedures yielded similar biological activity loss in the resultant labelled rt-PA and had half lives in the rat circulation of 1 and 3 min respectively. Complex formation of rt-PA was investigated by HPLC gel exclusion (TSK G3000 SW) fractionation of rat plasma samples taken 1-2 min after 125I-rt-PA injection. A series of radiolabelled complexes of varying molecular weights were found. However, 60% of the counts were associated with a single large molecular weight complex (350–500 kDa) which was undetectable by immunologically based assays (ELISA and BIA) and showed only low activity with a functional promoter-type t-PA assay. Two major activity peaks in the HPLC fractions were associated with Tree t-PA and a complex having a molecular weight of ̴ 180 kDa. HPLC fractionation to produce these three peaks at various timed intervals after injection of 125I-rt-PA showed each to have a similar initial rate half life in the rat circulation of 4-5 min. The function of these complexes as yet is unclear but since a high proportion of rt-PA is associated with a high molecular weight complex with a short half life in the rat, we suggest that the formation of this complex may be a mechanism by which t-PA activity is initially regulated and finally cleared from the rat circulation.
Keywords: Recombinant tissue plasminogen activator; Rat; Catabolic behaviour; HPLC